P039: The iterative evaluation and development of a core and high-acuity low-occurrence simulation-based procedures training program for emergency medicine trainees. (May 2019) - Dunne, C.; Chalker, J.; Bursey, K.; Parsons, M.
Abstract : Introduction : Competency-based skills development has driven the evolution of medical education. Simulation-based education is established as an essential tool to supplement clinical encounters and it provides the opportunity for low-stakes practice of common and high-acuity low-occurrence (HALO) procedures and scenarios. This is particularly important for emergency medicine trainees working to build confidence, knowledge, and skills in the field.Methods : In the procedural training sessions, learners rotate through 6 small-group stations over a 3-hour period. Skills topics are determined from faculty input, prior session feedback, and literature reviews. Topics included chest tubes, airway intervention, lumbar punctures and trauma interventions. Online content and brief written materials are used for pre-session learning. The small groups use hands-on faculty-guided training, with real-time feedback. Printed materials supplement key learning points at the stations. A combination of low-fidelity task trainers and simulated patients are used for practice and demonstration. R3 EM residents have the opportunity to mentor junior learners. Brief participant surveys are distributed at each session to gather qualitative and quantitative feedback.Results : Feedback forms were completed by 79/85 (92.9%) learners over a period of 4 years (2015-2018). Participants included medical students (11.8%), EM residents (52.9%), and non-EM residents (35.3%). 84.8% (67/79) gave positive qualitative feedback on the sessions, citing points such as the beneficial practice opportunities, quality of instruction, and utility of the models. Updated surveys (N = 26) used a 5-point Likert scale (1 = disagree strongly; 5 strongly agree) in addition to qualitative feedback. Participants indicated that sessions were valuable, and informative (M = 4.692, SD = 0.462; M = 4.270, SD = 0.710). They reported increased understanding of procedures discussed, and they were likely to recommend the session (M = 4.301, SD = 0.606; M = 4.808, SD = 0.394).Conclusion : The ongoing evaluation of our mentor guided hands-on low-fidelity and hybrid simulation-based procedural skills sessions facilitates meaningful programmatic changes to best meet the needs of EM learners. Sessions also provide a forum for EM resident mentorship of junior learners. Feedback indicates learners enjoyed the sessions and found this to be an engaging and effective instructional modality.